Conditions for Pension Liability to Become Zero Under Certain Actuarial Assumptions Imposed On International Accounting Standard 19 Actuarial Model - Michael Ogungbenle , Gbenga (Nepalese Journal of Insurance and Social Security, 2022)
The international accounting standards  employee benefits describe the accounting requirements for employee’s short-term, post-retirement, long-term and termination benefits. It further enshrines the principle that the cost of providing employee benefits should be recognized in the period over which benefits are earned by the employee and defines how each cohort of employee benefit is estimated. The objectives of this study are: (i) to estimate the liabilities of each members of the scheme under  model (ii) to establish the mathematical condition under which the funding standard liability will be zero. This study applies the funding standard models for the computations of accruing liabilities for the current and past service liability of employees. Data in respect of different categories of employees was collected from a government institution in Jos North local government of Plateau state, Nigeria. The data includes the employee’s annual salary and their respective demographic statistics. This was used to obtain the number of years of pensionable service completed and the future years of services to be completed before retirement at the age of years. The study further employs life annuity table to compute the service liability of each member of the scheme. From our results, computational evidence proves that the total service liability of the plan will be vanishingly zero when certain mathematical annuity assumptions are imposed and hence this represents the condition for which the liability of the plan to the members to be zero.